Pengaruh Store Atmosphere, Harga Produk Terhadap Kepuasan Pelanggan Di Minimarket Alfamidi Taman Pondok Jati Sidoarjo - Siti Samsiyah; Tri Ariprabowo (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background - Retail development in the digital era occurs in business competitors, namely minimarkets and department stores. Before the existence of minimarkets, people were more interested in shopping at traditional markets, but now there is technological development, so many people or consumers move to modern markets. Purpose - This study discusses the Store Atmosphere, product prices on customer satisfaction Alfamidi Minimarket Taman Pondok Jati Taman Sidoarjo. Design / Methodology / Approach - The research sample is 84 respondents, where the respondents here are visitors who do shopping at the Alfamidi Taman Pondok Jati minimarket, Sidoarjo. The research analysis uses the Multiple Linear Regression approach. The reliability and validity test of the questionnaire was carried out to enforce the accuracy of the questionnaire given to the respondents. Results and Discussion - The results of this study for partial hypothesis testing of store atmosphere variables, product prices affect customer satisfaction. A comfortable, safe atmosphere, affordable prices, and satisfying service will influence customers to return to the Minimarket. Conclusion - Product diversity is the completeness of the goods sold and the availability of the goods. So the Alfamidi Taman Pondok Jati Taman Sidoarjo Minimarket, the more diverse its products are complete and the satisfying service, the more sales will increase. Research Implications - Research can be used as a reference for franchise companies in enforcing problems in the retail sector, namely evaluation materials for (a) Companies that establish franchises (b) Alfamidi Minimarket Services as a retail sales place to meet community needs (c) Determine service strategies, product prices and marketing for the company.